PENGARUH UMUR, GENDER, DAN PENDIDIKAN TERHADAP PERILAKU RISIKO AUDITOR DALAM KONTEKS AUDIT ATAS LAPORAN KEUANGAN - Taufiequr R. Wirosari (Jurnal Ekonomi dan Bisnis Airlangga, 2017)
ABSTRACTThis research aims to examines and proves the influence of auditor’s risk behavior generated by age, gender, and education. This is important because risk is the main focus on Professional Standard on Auditing (PSA) as auditor guidance to audit of financial statement, so it is important to examine that auditor perception and propensity to face that risk.This study is a quantitative approach, which respondents are auditors involved in the audit of financial statements in Indonesian. The data was collected using a questionnaire Ionescu & Turlea (2011). This research using age (X1), gender (X2), and education (X3) as independent variable and auditor’s risk behavior (Y) as dependent variable. Hypothesis testing was performed using multiple linear regression with a 5% significance level. The result show age has a positive and significant influence on auditor’s risk behavior, in a financial audit context, while gender and education has not significant influence on auditor’s risk behavior.